Short run stock overreaction: evidence from Bursa Malaysia - Ali, Norli; Md Nassir, Annuar; Hassan, Taufiq; Zainal Abidin, Sazali (Faculty of Economics and Management, Universiti Putra Malaysia, 2010)
The objective of this paper is to discuss evidence of short run stock overreaction with respect to the arrival of dramatic events in the Malaysian stock market. The findings reveal that Malaysian stock market overreacts to economic crisis and extraordinary political events. The study shows significant overreaction behaviour existed in this market upon announcement of the removal of the deputy prime minister and announcement of the resignation of the prime minister. In contrast, evidence of underreaction was detected upon announcement of the national election. With regards to dramatic international events, Malaysian stock markets only disclose evidence of stock overreaction behaviour to SARS outbreak.